Bioremediation of Polycyclic Aromatic Hydrocarbon contaminated Aqueous-Soil matrix: Effect of co-contamination - CN Owabor; OC Onwuemene; I Enaburekhan (Journal of Applied Sciences and Environmental Management)
This study investigates the effect of lead and chromium on the rate of bioremediation of polycyclic aromatic hydrocarbon (PAH) contaminated clay soil. Naphthalene was used as a target PAH. The soil was sterilized by heating at 120oC for one hour. 100g of the soil was contaminated with lead, chromium, nickel and mercury (40-200mg/l), 200mg/l of naphthalene and finally inoculated with microbes (Bacillus spp and Aspergillus niger). A control experiment containing these microbes, naphthalene but without heavy metals served was also setup. Residual naphthalene concentration was taken and analysed every three (3) days. The result of the study showed that lead at 40mg/l, 80mg/l, 120mg/l, 160mg/l and 200mg/l had the following percentage degradation 84.45%, 75.68%, 70.23%, 60.49%, and 52.95% respectively, Chromium at the same concentrations had 83.89%, 74.95%, 69.99%, 59.95% and 52.89%, nickel had 82.49%, 71.89%, 62.86%, 49.89%, 42.34% while mercury had, 73.99%, 71.89%, 48.98%, 24.22% and 10.17% at the end of the 42 days contact period. The percent degradation for the control sample was found to be 85%. The observed percentages are an indicator that the rate of naphthalene degradation was faster in the control experiment and the results showed that heavy metals inhibited biodegradation of naphthalene by varying degrees. At concentrations of 40mg/l-200mg/l of the different heavy metals, there was a steady reduction in the biodegradation rate, which suggests an increase in the interference with the metabolic activity of the microbes. This can be attributed to the poor colonization of the microbes at these concentrations. @JASEM